Event-triggered containment control for multi-agent systems with switching topology in finite-time. (16th February 2023) - Wei, Wenjun; Lv, Jiahui; Gao, Fengyang; Yang, Liben
In this paper, a distributed finite-time state observer and event-triggered control strategy are proposed for the event-triggered multi-agent containment control in finite-time, while considering that the network topology is too brittle to switch due to disturbances and emergencies in actual communication. Firstly, we design a distributed control protocol through finite-time state observer under switching topology, which the follower agents can quickly converge to the convex hull formed by multiple leaders. The switching topology is more practical. We prove that the designed state observer can estimate the external system status in a finite-time by using graph theory and Lyapunov stability theory. Secondly, the event-triggered control mechanism is designed to reduce the communication times and the updating times between multi-agents and greatly decrease the energy consumption on the basis of satisfying the finite-time containment control. We also prove that the designed control strategy can eliminate Zeno behaviour. Finally, the effectiveness of the theoretical results is verified by a simulation example.